Invigorasi dan Pengaruhnya Terhadap Pertumbuhan Bibit Iles-iles (Amorphophallus muelleri Blume) (Invigoration and Its Impact on Seedling Growth of Iles-iles (Amorphophallus muelleri Blume)) - Edi Santosa; Anas Dinnurrohman Susila; Adolf Pieter Lontoh (IPB University, 2014)
The experiments of vacuum-asisted seed invigoration was conducted in Bogor, Indonesia, in order to increase crop production of iles-iles (Amorphophallus muelleri). This research was conducted in two series of experiments. The first experiment was conducted to determine the level of vacuum. The research was using 5 treatments i.e., control 1 (soaked in the water), control 2 (soaked in a solution of 2% N), control 3 (vacuum in water media), vacuum in solution containing 2% N, 4% N, 2% NPK (2:1:1), 4% NPK, vacuum in solution of supplementary liquid fertilizer (PPC) 2% and 4% PPC. The results of of the first experiment showed that the vacuum treatment increased the germination of iles-iles, the best vacuum pressure was -250mmHg. In the second experiment, the vacuum in a solution 4% PPC generated the highest growth followed by vacuum in 2% solution of NPK and 4% of PPC. In addition, the vacuum in the nutrient solution over 4% lead to inhibition of growth. The implication of this study is that the provision of nutrients in the seeds can increase plant growth of iles-iles. Vacuum treatment can enhance the effectiveness of invigoration.Keywords : NPK, PPC, seed treatment, starter solution, vacuum